2022
DOI: 10.1111/faf.12649
|View full text |Cite
|
Sign up to set email alerts
|

Managing fisheries for maximum nutrient yield

Abstract: Wild-caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutritionsensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Seafood statistics and research often defaults to a production perspective, with even consumption being measured in liveweight mass 1 . If human nutrition is the ultimate objective of fisheries and aquaculture, it is important that outputs are understood and evaluated on a nutritionally relevant basis particularly given the diversity of species involved 4 and maximising the nutritional output while minimising environmental costs of seafood provisioning should be a guiding principle for policy-making in these areas 41 . As both fisheries and aquaculture face many environmental challenges-in terms of sustainable utilisation of stocks, reduction of by-catch and impacts on local ecosystem structure and function, nutrient enrichment, and disease amplification-restricting the analysis of sustainability to GHG emissions may seem very limited.…”
Section: Resultsmentioning
confidence: 99%
“…Seafood statistics and research often defaults to a production perspective, with even consumption being measured in liveweight mass 1 . If human nutrition is the ultimate objective of fisheries and aquaculture, it is important that outputs are understood and evaluated on a nutritionally relevant basis particularly given the diversity of species involved 4 and maximising the nutritional output while minimising environmental costs of seafood provisioning should be a guiding principle for policy-making in these areas 41 . As both fisheries and aquaculture face many environmental challenges-in terms of sustainable utilisation of stocks, reduction of by-catch and impacts on local ecosystem structure and function, nutrient enrichment, and disease amplification-restricting the analysis of sustainability to GHG emissions may seem very limited.…”
Section: Resultsmentioning
confidence: 99%
“…Against site-specific BMMSY benchmarks, we found that 52 % of our sites open to extraction activities had median biomass values below their site-specific BMMSY from the Gompertz-Fox model (Fig. 1i) and only 49 [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] % of sites were in the range of producing "Pretty good multispecies yields" (PGMY, defined as the sustainable yield that is within 0.8 of MMSY (27; Fig. 1j).…”
Section: Status Of the World's Coral Reef Fisheries From A Long-term ...mentioning
confidence: 86%
“…Combining both standing stock biomass and catch estimates, we found that 54 [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] % of jurisdictions with both standing stock biomass and spatial catch data available had reef fisheries of "conservation concern" (4), failing one or both sustainable reference points based on weighted biomass values (Fig. 2e-f).…”
Section: Status Of the World's Coral Reef Fisheries From A Long-term ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stock biomass and corresponding target and limit reference points represent only some of the information that managers must consider when grappling with decisions that often involve trade-offs among competing objectives. Different benchmarks, for example considering B MSY as a limit rather than a target, or alternatives to MSY-based quantities such as maximum economic yield or focus on nutrient provision (Robinson et al, 2022), all involve societal as well as biological considerations that we do not address in this study. More broadly, best-practice management extends beyond evaluating single-population measures of relative biomass, also considering wider impacts of fishing activities on food webs and ecosystems.…”
Section: Discussionmentioning
confidence: 99%